Microalgae: the use of nanotechnology in biorremediation - Santini, Jéssica Cristine Viera Machado; Pena, Elisandra da Silva; de Sousa Filho, Walter Paixão; Mortari, Sérgio Roberto; Fernandes, Liana da Silva; de Souza, Diego; Bortoluzzi, Luisa Donato; Vieira, Wanessa de Carvalho; Sagrillo, Michele Rorato (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
Over the past two decades, great attention has been paid to managing environmental pollution caused by hazardous materials, such as: metals (lead, cadmium), pesticide residues, leakage of rights, among others. Many methods have been developed for the removal of such substances as precipitation, evaporation, ion exchange. However, these methods have several disadvantages such as: high cost of implantation, need for a large quantity of chemical products and interference of the process due to the presence of oils. It is known that there is a need to awaken more and more human and collective consciousness for the development and application of new technologies in favor of the environment. This review highlights the alternative biological agent abundantly present in nature, that is, microalgae as a possible sink for the removal of these toxic substances from the environment. Microalgae biomass has also been used to remove heavy metals, and in wastewater treatment facilities, they can be used to reduce the amount of toxic chemicals needed to clean and purify water, reaffirming its bio-absorption capacity toxic.